The Impact of Stress Level, Energy, Protein Intake Towards Nutritional Status in Class II B Lumajang Prison - Syani Indah Dian Nabila; Lulu' Luthfiya; Kartika Pibriyanti; Hafidhotun Nabawiyah; Erlik Sri Anjariyatun (Universitas Darussalam Gontor, 2023)
Background: Nutritional status is a condition of the body that arises from the balance between food intake and nutrient utilization. Prisoners have the right to receive proper healthcare and food according to their needs. Several factors can influence nutritional status, including food intake and the level of stress experienced by an individual. Additionally, the adequacy of nutrients, especially carbohydrates, fats, and proteins as energy sources, also plays a role in determining nutritional status. Objective: To analyze the relationship between stress level, energy intake, protein intake, and nutritional status among prisoners at the Class II B Lumajang Correctional Facility. Methods: This study employed an analytical observational approach with a cross-sectional design. The study population consisted of male prisoners at the Class II B Lumajang prison, and the total sample size was 92 individuals. The sampling technique used the Slovin formula with the quota sampling method. Data collection involved administering the DASS 42 questionnaire, measuring body weight and height, and recording 3x24-hour food recalls. The data were then analyzed using the Spearman test. Results: there was no significant relationship between stress level and nutritional status (p = 0.121), no correlation between energy intake and nutritional status (p = 0.508), and no association between protein intake and nutritional status (p = 0.645). Conclusion: Based on the findings, it can be concluded that stress level, energy intake, and protein intake are not factors that significantly affect the nutritional status of prisoners at Class II B prison.